Introduction - Mallari, Julieta C. (LIRIP Journal of Interdisciplinary Studies; Vol 3 (2020): LIRIP Journal of Interdisciplinary Studies, 2021)
Introduction to LIRIP Journal of Interdisciplinary Studies Volume 3 (2020)